2019
DOI: 10.1128/jvi.00475-19
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Mucosal Modified Vaccinia Virus Ankara Prime/Soluble gp120 Boost HIV Vaccination Regimen Induces Antibody Responses Similar to Those of an Intramuscular Regimen

Abstract: The benefits of mucosal vaccines over injected vaccines are difficult to ascertain, since mucosally administered vaccines often induce serum antibody responses of lower magnitude than those induced by injected vaccines. This study aimed to determine if mucosal vaccination using a modified vaccinia virus Ankara expressing human immunodeficiency virus type 1 (HIV-1) gp120 (MVAgp120) prime and a HIV-1 gp120 protein boost could be optimized to induce serum antibody responses similar to those induced by an intramus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…However, we selected a low antigen dose in our vaccine studies to increase the sensitivity of evaluating the adjuvant activity of our MCA small molecules. The antigen dose delivered intranasally in this study is lower than the antigen dose used by others in parenteral WNV vaccine studies (77,78) and we also reported that nasal immunization may require at least three times more antigen as parenteral immunization to induce a similar immune response (21). The vaccine conditions evaluated in this proof-of-concept study may not be optimal for induction of protective immunity against West Nile Virus; however, this study provides a foundation for further evaluation of mast cell activator small molecules as adjuvants for mucosal delivery.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…However, we selected a low antigen dose in our vaccine studies to increase the sensitivity of evaluating the adjuvant activity of our MCA small molecules. The antigen dose delivered intranasally in this study is lower than the antigen dose used by others in parenteral WNV vaccine studies (77,78) and we also reported that nasal immunization may require at least three times more antigen as parenteral immunization to induce a similar immune response (21). The vaccine conditions evaluated in this proof-of-concept study may not be optimal for induction of protective immunity against West Nile Virus; however, this study provides a foundation for further evaluation of mast cell activator small molecules as adjuvants for mucosal delivery.…”
Section: Discussionmentioning
confidence: 52%
“…The results from this study provide the support that MCAs are a new class of vaccine adjuvants for mucosal immunization. Mast cell activating polymeric compounds (5,13), peptides (21,22), and now, small molecules have been shown to enhance vaccine-specific immunity after nasal delivery. The hydrophobic nature of small molecules will require optimal formulations or medicinal chemical modifications to maximize compound activity and advance these compounds through the lead optimization phase of drug discovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potency of the nasal adjuvant activity of M7 agrees with recent results from our laboratory where M7 was used as a nasal vaccine adjuvant for HIV-1 gp120 in mice, rabbits and non-human primates. 29 Due to the common practice of administering cocaine to mucosal surfaces, the ability to promote strong, specific IgA responses against cocaine is a key advantage of a mucosal vaccine strategy and has the potential to more effectively neutralize cocaine that is administered via the nasal or oral mucosae. 4 Future studies may be required to evaluate Fig.…”
Section: Discussionmentioning
confidence: 99%